HYPERGLYCAEMIC EMERGENCY ADMISSION, POST-DISCHARGE CARE AND 6-MONTHS OUTCOME IN HOSPITAL BENTONG - M, Woh Wei; S, Chee Keong (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Diabetic ketoacidosis (DKA) and hyperglycemic hyperosmolar state (HHS) are two acute complications of diabetes with increased morbidity and mortality if not treated appropriately. Outcome and follow-up care of patients after recovery and discharge for DKA/HHS is relatively under-reported and unknown. The aim of this study was to assess DKA and HHS admission and postdischarge care and outcome. METHODOLOGY This is a cross-sectional study including all patients with DKA and HHS admitted to Hospital Bentong from January 2017 to December 2018. Clinical records were reviewed for demographics, DKA/HHS characteristics, post-discharge care and diabetes control after 6 months. RESULTS 44 patients with validated hyperglycemic emergency diagnosis were recorded during study period. 70.5% (n=31) for DKA and 29.5% (n=13) for HHS admission. Mean age of patients was 55.5 years old (SD 16) with predominantly females 55% (n=24). 90% (n=40) of patients had Type 2 diabetes mellitus. Two (4.5%) patients had diabetic emergency as first presentation of diabetes diagnosis. 6.8% (n=3) of the patients required ventilation www.asean-endocrinejournal.org 2019 MEMS Annual Congress 20 www.asean-endocrinejournal.org Poster Abstracts (Adult | Paediatric | Basic Science) and ICU admission. Mean length of hospital stay was 5.8 (SD 3.7) days and mortality rate was 6.8%. Upon discharge, 38.6% (n=17) followed-up in nearby health clinics, 20.4% (n=9) in medical outpatient department (OPD), 15.9% (n=7) in general OPD, 13.6% (n=6) in other hospitals and 4.5% (n=2) with private GPs. 6.8% (n=3) of patients defaulted their follow-up in Hospital Bentong (MOPD and OPD) with unknown outcomes. Patients who had follow-up in Hospital Bentong, had 6.25% readmission rate within 6-months of discharge with no documented mortality. Mean HbA1c was 10.67% (SD 3.68). 62.5% (n=10) of patients had documented proteinuria. 75% (n=12) of patients were on insulin therapy with mean total daily dose of 49.5 (SD 9.7) units. CONCLUSION There are significant pitfalls in follow-up of patients after hyperglycaemic emergency admission, evidently with poor glycaemic control. A standardized follow-up protocol with comprehensive monitoring is needed for these patients with continuous emphasis on glycaemic targets to prevent diabetic complications.